The provisions relating to wages in international agreements and treaties and the Qatari labor law: Comparative study - ALmaasfeh, Nashat Mfudi; Altarawneh, Hani Jamel (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to clarify what workers and their rights mean by reviewing the legal texts mentioned in their regard in international charters as well as in Qatari legislation The study concluded with a set of results, the most important of which are: The rights of workers are guaranteed within international charters (treaties and agreements), and among these rights is the right to remuneration. It is guaranteed within the Qatari national legislation, especially in the Qatari Labor Law No. 14 of 2004 AD, The State of Qatar has also issued Law No. 17 of 2020 AD on determining the minimum wage for workers and domestic workers. The study came out with a set of recommendations, including: The international community must find new, developed and applicable mechanisms that contribute to implementing what was stated in international conventions and covenants, especially those affecting human dignity, In addition to the importance of sustainable awareness raising in the areas of workers’ rights, if the awareness-raising methods are new to enable information to reach all workers groups of different educational and cultural levels.